Results of the 20th Congress of the Communist Party of China: a new message to the world - Ospanova, Zh.Ye. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2024)
China is rightfully recognized as one of the largest economies in the world and an important political player in the international arena. The dynamic and continuous development of the country’s economic component, even in the post-COVID period, gives China a powerful impetus to further maintain the country’s stability and image throughout the world. Today it is impossible not to listen to the events taking place in China. Every five years, China hosts congresses of the ruling Communist Party, at which important vectors of development for the coming years are traditionally determined, urgent tasks are set, and ideological decisions are made. Given the importance of the PRC in the world community, party congresses are increasingly attracting attention and are being vigorously discussed on the sidelines of foreign governments. The 20th Congress of the Communist Party of China has become a resonant and historic event not only for the entire Chinese people, but also for countries that have close ties with China. In this study, we applied the method of modern structural functionalism, as well as political science, historical and sociological research methods. The article attempts to analyse the opinions of foreign experts, through the prism of which it is possible to see the situation in China in more detail. As a result of the research, an understanding of the main priorities of the new administration was reached, which carry important aspects of China’s political landscape.